PENGELOLAAN PERSURATAN DAN KEARSIPAN OLEH KEPALA KETATAUSAHAAN DI SMP N 5 KOTA SOLOK - Lusi Meli Gustia (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
Abstract: The purpose of this study was to determine: planning correspondence, planning archives and evaluating correspondence and archives in the administration of SMP Negeri 5 Solok City. This type of research is descriptive qualitative. The data sources in this study were the administrative head of SMP Negeri 5 Solok City, operators, and the administrative ranks of SMP Negeri 5 Solok City. Data collection techniques using interview techniques, documentation and observation. Data analysis techniques through qualitative analysis, namely; data reduction, data presentation, and conclusion drawing. The results of the study indicate that: (1) planning for correspondence and archives in the administration of SMP Negeri 5 Solok City includes two activities, namely planning a general field work program based on an operational plan as a guide for carrying out tasks and determining activity facilities in accordance with the school work program; (2) the implementation of archiving at SMP Negeri 5 Solok City includes four activities, namely filing letters, teaching teacher attendance lists, diplomas, certificates, educator certificates, duplicating official reports, tidying incoming and outgoing letters neatly into orders or folders based on classification and carry out the preparation of archives; (3) evaluation of correspondence and archives at SMP Negeri 5 Solok City provides convenience in accessing information and retrieving archives quickly when needed and carrying out activity reports properly according to the specified time.